Skin Infections in the Grappling Arts - Brian Jones (Universidad de León, 2012)
This article covers the incidence, symptoms, and treatment of skin infections common among grapplers. The purpose is to educate grapplers, coaches, and parents about the risk of skin infections, identification of infections, and steps to treat and prevent outbreaks. The information in this article is drawn from primary and medical reference literature. It is concluded that prevention is key and the appropriate measures should be taken to prevent the spread of infections. Grapplers of all styles should adhere to the guidelines set forth by the NCAA Wrestling Handbook when determining eligibility for practice or competition.